APPLICATION INFORMATION ACADEMIC AND STUDENT ADMINISTRATION (BAAK) IN STMIK JAKARTA STI&K USING PROTOCOL WIRELESS APPLICATION (WAP) - Anak Agung Sri Rahayu; Yudi Irawan Chandra, SKom., MMSI (Jurnal Sistem Informasi, 2004)
Applications using Wireless Application Protocol technology (WAP), enablingapplications that can be displayed and made accessible with wireless hardware, sothat information retrieval can be more effective and efficient. Media are used tocapture information that is mobile phone (mobile phone), which is a very appropriatemedium and easy to socialize. This application form displayed text on the screenphone users. This application can be accessed by mobile phone already has thetechnology General Packet Radio Service (GPRS)